Transcriptomic and proteomic analyses provide insights into host adaptation of a bamboo-feeding aphid - Zhang, Hui; Lin, Ruixun; Liu, Qian; Lu, Jianjun; Qiao, Gexia; Huang, Xiaolei (Frontiers in Plant Science, 2023)
Salivary glands and their secreted proteins play an important role in the feeding process of sap-sucking aphids. The determination of saliva composition is an important step in understanding host plant adaptation of aphids. Pseudoregma bambucicola is a severe bamboo pest in subtropical areas and the only aphid species that can exclusively feed on hard stalks of bamboos. How this species can penetrate and degrade hard bamboo cell walls and utilize a very specialized niche are important unanswered questions. Here, transcriptomic and mass spectrometry (LC-MS/MS) analyses were performed to characterize the gene/protein repertoire in salivary glands and secreted saliva of P. bambucicola. Some secretory proteins homologous to known aphid effectors important for aphid–plant interactions, such as digestive enzymes, detoxifying and antioxidant enzymes and some effectors modulating plant defenses, are also detected in salivary gland transcriptome and salivary gland and/or saliva secretomes in P. bambucicola. This indicates that these effectors are probably be essential for enabling P. bambucicola feeding on bamboo host. Although several plant cell wall degrading enzymes (PCWDEs) can be identified from transcriptome, most of the enzymes identified in salivary glands showed low expression levels and they only represent a small fraction of the complete set of enzymes for degrading cellulose and hemicellulose. In addition, our data show that P. bambucicola has no its own ability to produce pectinases. Overall, our analyses indicate that P. bambucicola may lose its own ability to express and secrete key PCWDEs, and its adaptation to unique feeding habit may depend on its symbiotic bacteria.